TASKS WITH AN INTEGRATIVE CONTENT AIMED AT DEVELOPING STUDENTS' PROFESSIONAL COMPETENCES AND REQUIREMENTS FOR THEM - Ismoilov Elmurod Olloberdi o‘g‘li (Western European Studies, 2024)
This article details the concepts of science integration and integrated education, as well as the importance of an integrative approach to the educational process. The content of materials on the development of professional competence of students and the principles of their selection are given. The analysis fully justifies the need to use the integration of disciplines in the education system to develop students' professional competencies.
Keywords: competence; professional competence; integration